Measuring Up : The Promises and Pitfalls of Performance Indicators in Higher Education. ASHE-ERIC Higher Education Report No. 5 - Gaither, Gerald; Association for the Study of Higher Education; ERIC Clearinghouse on Higher Education; George Washington Univ., Washington, DC. Graduate School of Education and Human Development (Washington, DC : ERIC Clearinghouse on Higher Education, 1994)
This report examines the development and implementation of performance indicators in higher education, focusing on the factors driving increased demand for accountability in higher education and the use of performance indicators in the United States and other countries. It discusses the public and political concern for increased productivity, accountability, and quality assessment at colleges and universities in the United States and other countries, in light of educational retrenchment and budgetary constraints. It then reviews the use of performance indicators and outcomes measures in the United States, focusing on the National Association of College and University Business Officers (NACUBO) benchmarking project, the Peterson's/AGB (Association of Governing Boards of Universities and Colleges) strategic indicators survey, the National Center for Higher Education Management Systems (NCHEMS) indicators of good practice project, and the Education Commission of the States (ECS) project. It then examines the use of performance indicators in Great Britain, Canada, Australia, The Netherlands, Finland, Sweden, and Denmark. The report concludes by discussing possible future trends in the use of performance indicators by governments and institutions to promote productivity, accountability, and quality in higher education. A list of related publications is included. (Contains approximately 500 references.) (MDM)
Availability: ERIC Clearinghouse on Higher Education, One Dupont Circle, N.W., Suite 630, Washington, DC 20036-1183 ($18 plus $3.75 postage).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RR93002008.
ERIC Note: For a digest of this report, see HE 028 391.
Microfiche.
Keywords: Accountability; Benchmarking; College Outcomes Assessment; Colleges; Cross Cultural Studies; Educational Policy; Educational Quality; Foreign Countries; Government Role; Higher Education; Institutional Evaluation; Outcomes of Education; Performance Factors; Productivity; Universities; Performance Indicators; Australia -- Canada -- Denmark -- Finland -- Great Britain -- Netherlands -- Sweden -- United States; ERIC Publications; Reports, Descriptive